Glucose deprivation and identification of TXNIP as an immunometabolic modulator of T cell activation in cancer - Dubuisson, Agathe; Mangelinck, Adèle; Knockaert, Samantha; Zichi, Adrien; Becht, Etienne; Philippon, Wendy; Dromaint-Catesson, Sandra; Fasquel, Manon; Melchiore, Fabien; Provost, Nicolas; Walas, Dawid; Darville, Hélène; et al. (Frontiers in Immunology, 2025)
BackgroundThe ability of immune cells to rapidly respond to pathogens or malignant cells is tightly linked to metabolic pathways. In cancer, the tumor microenvironment (TME) represents a complex system with a strong metabolism stress, in part due to glucose shortage, which limits proper T cell activation, differentiation and functions preventing anti-tumor immunity.MethodsIn this study, we evaluated T cell immune reactivity in glucose-restricted mixed lymphocyte reaction (MLR), using a comprehensive profiling of soluble factors, multiparametric flow cytometry and single cell RNA sequencing (scRNA-seq).ResultsWe determined that glucose restriction potentiates anti-PD-1 immune responses and identified thioredoxin-interacting protein (TXNIP), a negative regulator of glucose uptake, as a potential immunometabolic modulator of T cell activation. We confirmed TXNIP downregulation in tumor infiltrating T cells in cancer patients. We next investigated the implication of TXNIP in modulating immune effector functions in primary human T cells and showed that TXNIP depletion increased IFN-γ secretion and tumor cell killing.ConclusionsTXNIP is at the interface between immunometabolism and T cell activation and could represent a potential target for immuno-oncology treatments.